2021
DOI: 10.1016/j.mayocp.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic Risk in Hospitalized and Nonhospitalized COVID-19 Patients

Abstract: Objective An unexpectedly large number of people infected with Covid-19 had experienced a thrombotic event. This study aims to assess the associations between Covid-19 infection and thromboembolism including myocardial infarction (MI), ischaemic stroke, deep-vein thrombosis (DVT), and pulmonary embolism (PE). Patients and Methods A self-controlled case-series study was conducted covering the whole of Scotland’s general population. The study population comprised individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 28 publications
4
46
1
1
Order By: Relevance
“…7 Consistent with this, a self-controlled study of the Scottish general population has found that while the likelihood of thromboembolism was highest in the 7 days following a positive test, the risk remained significantly elevated 8 weeks later. 51 Similarly, a recent study using the US Veterans Affairs health databases showed an increased risk of PE beyond the first 30 days after a positive COVID-19 test compared with contemporary and historical controls. 52 Another USA-based study showed an increased risk of PE and pulmonary hypertension beyond the acute phase of COVID-19 infection, compared with contemporary and historical controls.…”
Section: Discussionmentioning
confidence: 93%
“…7 Consistent with this, a self-controlled study of the Scottish general population has found that while the likelihood of thromboembolism was highest in the 7 days following a positive test, the risk remained significantly elevated 8 weeks later. 51 Similarly, a recent study using the US Veterans Affairs health databases showed an increased risk of PE beyond the first 30 days after a positive COVID-19 test compared with contemporary and historical controls. 52 Another USA-based study showed an increased risk of PE and pulmonary hypertension beyond the acute phase of COVID-19 infection, compared with contemporary and historical controls.…”
Section: Discussionmentioning
confidence: 93%
“…5 In contrast, fewer clinical interventions have been implemented to prevent VTE among ambulatory patients with SARS-CoV-2 infection, partially because of conflicting findings on the association between the infection and VTE occurrence, with cohort studies showing no elevated risk 6 but self-controlled case series studies consistently showing a substantial increase of short-term risk. [7][8][9] Also, mixed evidence of benefit from oral anticoagulation complicated clinical decisions for ambulatory COVID-19. 10 Given the ongoing global rollout of vaccines, relaxation of public health restrictions, and the widespread highly transmissible Omicron variant, the absolute number of milder COVID-19 cases treated in ambulatory settings continues to rise worldwide.…”
mentioning
confidence: 99%
“…Early during the COVID-19 pandemic, it was recognized that infection with SARS-CoV-2 was associated with an increased risk of both arterial and venous thrombotic complications. This association is strongest for venous thromboembolic disease, but the risk of myocardial infarction (MI) is approximately doubled in the 7 days after COVID-19 diagnosis . Multiple studies have suggested worse outcomes in patients with COVID-19 and MI, with direct effects of the virus on endothelial cells, increased propensity for vascular thrombosis, and deficient care delivery all mechanistically implicated …”
mentioning
confidence: 99%